2020
DOI: 10.3390/foods9121797
|View full text |Cite
|
Sign up to set email alerts
|

1H NMR Spectroscopy to Characterize Italian Extra Virgin Olive Oil Blends, Using Statistical Models and Databases Based on Monocultivar Reference Oils

Abstract: During the last few years, the global demand for extra virgin olive oil (EVOO) is increased. Olive oil represents a significant percentage of world fat consumption determining an important development of its market. In this context, the problems related to counterfeiting and product fraud is becoming extremely relevant. Thus, the quality and authenticity control of EVOOs is nowadays mandatory. In this study we focused on the use of 1H NMR technique associated with multivariate statistical analysis to character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 41 publications
0
21
0
1
Order By: Relevance
“…This may have a meaning, since Italian oils with lower oleic and polyphenol contents could be used in larger quantities than oils with higher polyphenol contents, resulting in similar final characteristics of the blends. Indeed, an optimal level of bitterness is usually achieved finely trimming the high polyphenols oil constituents of a blend [ 50 ]. Focusing on the Italian oils as part of international blends it should be considered that they mainly consist of Coratina based blends [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This may have a meaning, since Italian oils with lower oleic and polyphenol contents could be used in larger quantities than oils with higher polyphenol contents, resulting in similar final characteristics of the blends. Indeed, an optimal level of bitterness is usually achieved finely trimming the high polyphenols oil constituents of a blend [ 50 ]. Focusing on the Italian oils as part of international blends it should be considered that they mainly consist of Coratina based blends [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Focusing on the Italian oils as part of international blends it should be considered that they mainly consist of Coratina based blends [ 51 ]. Interestingly, although specific EVOOs components content may vary according to several agronomic [ 52 ] and/or processing [ 53 ] factors, Coratina based oils generally represent a relevant part of the overall Italian production [ 50 ] and are well known for being rich in both oleic and polyphenols [ 51 , 52 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, NMR has proven to be an efficient technique in the fatty acid characterization of olive oil samples, enabling the assessment of fatty acid profiles as well as the ratio between different acyl groups, playing a crucial role in the study of the quality of these edible oils, the screening of the oxidation and deterioration process, the assessment of purity and authenticity and adulteration practices [ 10 ]. Indeed, NMR is a robust quantitative analytical technique used to obtain “high-throughput” spectroscopic and structural information on a wide range of molecular compounds [ 11 , 12 , 13 , 14 ]. The main advantages of NMR analysis are that (i) it can be used without using specific standards, (ii) it provides structural information, (iii) it is a non-destructive method, (iii) one can analyze simultaneously various components in a mixture without pre-isolation and (4) it requires a relatively short analysis time compared to other conventional analytical techniques (such as GC and HPLC), and the preparation of the sample is very simple and rapid [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the same way, Tapp et al [ 13 ] and De Luca et al [ 14 ] also applied FTIR spectroscopy for cluster analysis and the classification of 60 different olive oils originating from four European countries and Morocco, both reporting satisfactory results. Another analytical method used for the analysis of olive oils is Nuclear Magnetic Resonance (NMR) [ 15 , 16 ]. In the review of Dais et al [ 17 ], useful information can be found covering various aspects of NMR analysis of olive oils, such as the NMR instrumentation, sample preparation, and statistical analysis of NMR data, as well as information regarding the geographical and botanical discrimination of olive oils.…”
Section: Introductionmentioning
confidence: 99%